The Relationship of Fast Food Consumption Patterns with the Incidence of Obesity in School-Age Children in SDN 27 South Cities Gorontalo City - Fikri Haykal Rahman; Zainuddin; Cindy Puspita Sari Haji Jafar (Universitas Muhammadiyah Palu, 2026)
The problem of obesity in school-age children is still a nutritional problem that needs attention because it can have an impact on children's health and growth. One of the factors that is suspected to be related is the consumption pattern of fast food that is high in calories, fat, sugar, and sodium, so that there is a risk of increasing the incidence of obesity. This study aims to determine the relationship between fast food consumption patterns and the incidence of obesity in school-age children at SDN 27 Kota Selatan, Gorontalo City. This study uses a quantitative design with a cross-sectional approach. The sample totaled 151 respondents with a total sampling technique. The instruments were in the form of a questionnaire on fast food consumption patterns and anthropometric measurements of body weight and height to determine nutritional status. Data analysis using the Chi-Square test. The results showed that most of the respondents had fast food consumption patterns in the frequent category as many as 78 respondents (51.7%) and the rare category as many as 64 respondents (42.4%). Based on nutritional status, 78 respondents (51.7%) were in the obesity category. The results of the Chi-Square test showed that there was a significant relationship between fast food consumption patterns and the incidence of obesity with a p-value = 0.000 (p < 0.05). The conclusion of the study shows that there is a relationship between fast food consumption patterns and the incidence of obesity in school-age children, so it is hoped that these results can be educational material for health workers in preventing obesity through improving healthy diets in children and strengthening the role of parents in limiting fast food consumption and forming healthy eating habits from an early age in the family and school environment.